2017
DOI: 10.1016/j.redox.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Winter to summer change in vitamin D status reduces systemic inflammation and bioenergetic activity of human peripheral blood mononuclear cells

Abstract: BackgroundVitamin D status [25(OH)D] has recently been reported to be associated with altered cellular bioenergetic profiles of peripheral blood mononuclear cells (PBMCs). No study has tracked the seasonal variation of 25(OH)D and its putative influence on whole body energy metabolism, cellular bioenergetic profiles, inflammatory markers and clinical chemistry.Material and methodsWhole body energy metabolism and substrate utilisation were measured by indirect calorimetry. PBMCs obtained from the same subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…CRP also increased, but there was no statistically signifi cant difference. The higher levels of proinfl ammatory cytokines in winter were reported to be associated with lower levels of vitamin D in winter (42). In the current study, vitamin D levels were not evaluated, but in RA patients, the DAS 28 level was higher in winter than in summer.…”
Section: Discussionmentioning
confidence: 64%
“…CRP also increased, but there was no statistically signifi cant difference. The higher levels of proinfl ammatory cytokines in winter were reported to be associated with lower levels of vitamin D in winter (42). In the current study, vitamin D levels were not evaluated, but in RA patients, the DAS 28 level was higher in winter than in summer.…”
Section: Discussionmentioning
confidence: 64%
“…In the last decade, the interrelation between bone and carbohydrate metabolism has been a particular subject of research [12][13][14]. However, studies assessing the impact of systematic physical activity on bone and metabolic indices should take the significant problem that outdoor physical activity can increase exposure to ultraviolet (UV) radiation into account, which might modify bone and carbohydrate metabolism by altering the serum concentration of 25(OH)D [15], regardless of the influence of the mechanical stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is a novel independent predictor of resting metabolic rate in adults [20] and research that was conducted on animal models has shown that it plays an important role in the regulation of energy balance [21]. It was documented that seasonal variations in serum 25(OH)D concentration, due to changes in UV intensity, lead to changes in energy metabolism [15]. Melin et al [22] observed that, among elderly people, regular daylight exposure during the summer enhanced 25(OH)D levels and improved calcium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, vitamin D also exhibits anti‐inflammatory effects . In vitro studies have shown that vitamin D reduces UV‐induced damage, including inflammation, sunburn, and photo‐associated immunosuppression, and carcinogenesis, while a human epidemiology study associated higher vitamin D status with reduced systemic inflammation . When topically applied to human skin, Vitamin D reduces polymorphic light eruption …”
Section: Discussionmentioning
confidence: 99%
“…19 In vitro studies have shown that vitamin D reduces UV-induced damage, including inflammation, F I G U R E 1 Mean percent change in minimal erythema dose (MED) compared with baseline after supplementation for 4 and 8 wk sunburn, and photo-associated immunosuppression, and carcinogenesis, [20][21][22] while a human epidemiology study associated higher vitamin D status with reduced systemic inflammation. 23 When topically applied to human skin, Vitamin D reduces polymorphic light eruption. 24 Currently, it is difficult to ascertain the relative contribution of each compound within the Bend Skincare Anti-Aging Formula or any possible synergies, due to insufficient data for comparison.…”
Section: Discussionmentioning
confidence: 99%